Quasilinear and nonlinear dynamics of energetic-ion-driven Alfvénic eigenmodes - Duarte, Vinícius Njaim (2017)
The destabilization of plasma waves upon their interaction with fast ions is studied using a kinetic framework. The work consists of two parts: (I) a study of the applicability of quasilinear theory using a pertubative, early-time nonlinear evolution of a mode and its prediction with respect to chirping oscillations, and (II) the resonance-broadened quasilinear formulation of the evolution of unstable modes. In part I, we have developed predictive capabilities for the type of fast-ion-induced transport by means of a criterion for the likelihood of a mode to oscillate at a constant frequency or to evolve to a bifurcation consisting of nonlinear chirping oscillations. The proposed criterion is derived and evaluated using the linear codes NOVA and NOVA-K. The criterion was shown to be in agreement with experimentally observed modes in the tokamaks DIII-D and NSTX. The analysis reveals that micro-turbulence is a key mediator for suppressing chirping and therefore allowing quasilinear theory to be applicable. In part II, a system of resonance-broadened quasilinear equations (RBQ) was derived using action and angle variables, which takes advantage of system symmetries by using the invariants of the unperturbed motion as variables when accounting for the effects of perturbations due to modes. The equations capture information on mode structures and on resonances that are spread over phase space. We then expressed them in terms of NOVA code notation. The RBQ model is presented, along with the finite-difference scheme used for numerical integration. Numerical results and future developments are also described.